Design of an Innovative Helical Antenna for Aerial Platforms to Enable Jam Resistant Reception of GNSS Signals - Inammullah Khan (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2019)
This paper describes the design of a helical antenna at GPS upper L band frequency. Helical antennas are widely used in airborne and space borne applications to receive GNSS signals. One major concern in reception of GNSS signals is their susceptibility to jamming signals. To address this problem a novel antenna design is proposed in this paper. The proposed design provides lower side lobe levels than conventional helical antennas, without compromising efficiency of the antenna. The lower side lobe levels are the key feature in making the antenna less susceptible to jamming signals. Moreover, despite being smaller than classically designed helical antennas this design can handle relatively more power. To achieve these results the key parameters of helical antennas, namely, dimensions and shape of helix antenna i.e. height, radius, number of turns, thickness as well as pitch angle were optimized. In addition, the ground effect was used to supplement the desired results. Detailed simulation results using CST Microwave Studio software have been computed. These results are then compared with the results for standard helical antenna to validate and verify the advantage of using the proposed design.